2019
DOI: 10.3390/nu11061198
|View full text |Cite
|
Sign up to set email alerts
|

Improving the Dietary Vitamin A Content of Rural Communities in South Africa by Replacing Non-Biofortified White Maize and Sweet Potato with Biofortified Maize and Sweet Potato in Traditional Dishes

Abstract: Biofortification of staple crops has a potential for addressing micronutrient deficiencies, such as vitamin A deficiency (VAD), which are prevalent in South Africa. The poor acceptability of provitamin A (PVA)-biofortified foods could be improved by combining them with other food items to produce modified traditional dishes. The nutritional composition of the dishes could also be improved by the modification. The study aimed to investigate the effect of replacing white maize and cream-fleshed sweet potato (CFS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
13
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 37 publications
6
13
1
Order By: Relevance
“…The lower protein content in yellow compared to white maize is in agreement with the results obtained by Cantaluppi et al [21]. Govender et al and Nkosi et al [22,23] reported 10.22% and 10.10% protein on white maize, respectively which are higher than the values determined in the present study.…”
Section: Macro-nutrients Analysissupporting
confidence: 93%
See 1 more Smart Citation
“…The lower protein content in yellow compared to white maize is in agreement with the results obtained by Cantaluppi et al [21]. Govender et al and Nkosi et al [22,23] reported 10.22% and 10.10% protein on white maize, respectively which are higher than the values determined in the present study.…”
Section: Macro-nutrients Analysissupporting
confidence: 93%
“…Nkosi et al [23] reported 29.9% fibre on white maize, this finding agrees with results of this study. Govender et al [22] reported 5.44% fibre on white maize which is lower than results of the present study.…”
Section: Macro-nutrients Analysiscontrasting
confidence: 85%
“…There is substantial evidence proving the efficacy and effectiveness of biofortified crops in increasing micronutrient intake and improving health status in humans [81][82][83][84][85][86][87][88][89]. Hitherto, only two effectiveness studies have been conducted with biofortified crops, both assessing provitamin A biofortified sweet potato.…”
Section: Discussionmentioning
confidence: 99%
“…The provitamin A-biofortified maize coded PVA A is an experimental type; it has not been commercialized, and hence does not have a variety name. The maize grain was produced by plant breeders from the University of KwaZulu-Natal (UKZN) and milled into maize for this study using methods described by Govender et al [37]. Two varieties of sweet potato were selected for this study, OFSP (A45) and CFSP (A40).…”
Section: Methodsmentioning
confidence: 99%
“…For example, a study conducted by Amod et al found that when PVA-biofortified maize porridge was combined with chicken stew its acceptability increased [36]. Additionally, PVA-biofortified composite dishes could improve the nutritional intake of vulnerable individuals [37]. A major problem in South Africa is poverty; it is a leading contributing factor to food and nutrition insecurity [38].…”
Section: Introductionmentioning
confidence: 99%